Sleep after learning aids the consolidation of factual knowledge, but not relearning - Cousins, James N (Sleep, 2020)
STUDY OBJECTIVES: Sleep strengthens and reorganizes declarative memories, but the extent to which these processes benefit subsequent relearning of the same material remains unknown. It is also unclear whether sleep-memory effects translate to educationally realistic learning tasks and improve long-term learning outcomes. METHODS: Young adults learned factual knowledge in two learning sessions that were 12 h apart and separated by either nocturnal sleep (n = 26) or daytime wakefulness (n = 26). Memory before and after the retention interval was compared to assess the effect of sleep on consolidation, while memory before and after the second learning session was compared to assess relearning. A final test 1 week later assessed whether there was any long-term advantage to sleeping between two study sessions. RESULTS: Sleep significantly enhanced consolidation of factual knowledge (p = 0.01, d = 0.72), but groups did not differ in their capacity to relearn the materials (p = 0.72, d = 0.10). After 1 week, a numerical memory advantage remained for the sleep group but was no longer significant (p = 0.21, d = 0.35). CONCLUSIONS: Reduced forgetting after sleep is a robust finding that extends to our ecologically valid learning task, but we found no evidence that sleep enhances relearning. Our findings can exclude a large effect of sleep on long-term memory after 1 week, but hint at a smaller effect, leaving open the possibility of practical benefits from organizing study sessions around nocturnal sleep. These findings highlight the importance of revisiting key sleep-memory effects to assess their relevance to long-term learning outcomes with naturalistic learning materials.